1997
DOI: 10.1193/1.1585946
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Retrofitting of Rectangular Bridge Columns with Composite Straps

Abstract: Behavior of typical rectangular bridge columns with substandard design details for seismic forces was investigated. The poor performance of this type of column attested to the need for effective and economical seismic upgrading techniques. A method utilizing fiber reinforced polymer (FRP) composites to retrofit existing bridge columns is investigated in this paper. High-strength FRP straps are wrapped around the column in the potential plastic hinge region to increase confinement and to improve the behavior un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…By contrast, FRP jackets have been extensively studied experimentally, including rectangular columns with deformed bars lap-spliced in the plastic hinge zone (Chang et al 2001;Elnabelsy et al 2004;Haroun et al 2001;Harries et al 2003;Saadatmanesh et al 1997a;Saadatmanesh et al 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, FRP jackets have been extensively studied experimentally, including rectangular columns with deformed bars lap-spliced in the plastic hinge zone (Chang et al 2001;Elnabelsy et al 2004;Haroun et al 2001;Harries et al 2003;Saadatmanesh et al 1997a;Saadatmanesh et al 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…Saadatmanesh et al1996Saadatmanesh et al ,1997Seible et al1997;Ma and Xiao1999; Harries et al2006;Bousias et al 2006;Breña andSchlick2007;Youm et al2007;Harajli and Dagher2008;Harajli andKhalil 2008;Elgawady et al2010;Elsouri andHarajli2011;Bournas andTriantafillou 2011). Despite the extensive researcheffort, only a few design models existfor the strengthening ofcolumnsplicesusingFRP materials.…”
mentioning
confidence: 99%
“…Cantilever columns have been extensively tested in the past (Priestley et al 1992, Saadatmanesh et al 1996, Saadatmanesh et al 1997b, Saadatmanesh et al 1997a, Seible et al 1997, Xiao and Ma 1997, Haroun et al 1999, Ma and Xiao 1999, Chang et al 2000, Ma et al 2000, Chang et al 2001, Saatcioglu and Elnabelsy 2001, Haroun et al 2003, Elnabelsy and Saatcioglu 2004, Sause et al 2004, Schlick and Breña 2004, Yalçin and Kaya 2004, Bousias et al 2006, Bousias et al 2007, Breña and Schlick 2007, Youm et al 2007, Chung et al 2008, Eshghi and Zanjanizadeh 2008, Harajli 2008, ElGawady et al 2010, Bournas and Triantafillou 2011, Kim et al 2011. Column specimens are usually cast on a stiff concrete block simulating the structure's foundation, as shown in Figure 1.…”
Section: Capacity-ductility Approach: Tests On Cantilever Columnsmentioning
confidence: 99%
“…Typical applications involve bonding FRP fabric sheets or precured shells around a column to provide additional confinement (see Figure 1(a)), thus enhancing the lap bond strength and preventing a premature splitting failure. In the last decades, extensive experimental research has confirmed the effectiveness of FRP confinement at improving the behaviour of RC members with inadequate short lapped bars (Aboutaha et al 1996, Saadatmanesh et al 1996, Saadatmanesh et al 1997b, Seible et al 1997, Tastani and Pantazopoulou 2001, Bousias et al 2006, Harries et al 2006, Ghosh and Sheikh 2007, Harajli and Dagher 2008, ElGawady et al 2010, Bournas and Triantafillou 2011. Due to the large number of parameters affecting the bond behaviour of lapped bars, different experimental and analytical approaches were adopted to evaluate the effectiveness of FRP confinement.…”
Section: Introductionmentioning
confidence: 99%